2012
DOI: 10.1007/s10735-011-9390-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of thymoquinone against cholestatic oxidative stress and hepatic damage after biliary obstruction in rats

Abstract: The aim of this study was to examine the preventive and therapeutic effects of thymoquinone (TQ) against cholestatic oxidative stress and liver damage in common bile duct ligated rats. A total of 24 male Sprague-Dawley rats were divided into three groups: control, bile duct ligation (BDL) and BDL + received TQ; each group contain 8 animals. The rats in TQ treated groups were given TQ (50 mg/kg body weight) once a day orally for 2 weeks starting 3 days prior to BDL operation. To date, no more biochemical and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…The Cd-treated group was injected subcutaneously with CdCl2 dissolved in saline in the amount of 2 ml/kg/day for 30 days, resulting in a dosage of 1 mg/kg Cd [18]. The rats in the TQ-treated group were given TQ (50 mg/kg body weight) [13] once a day orally together with first Cd injection during the study period. At the end of the experiment, all rats were sacrificed by decapitation under ketamine-xylazine anesthesia.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cd-treated group was injected subcutaneously with CdCl2 dissolved in saline in the amount of 2 ml/kg/day for 30 days, resulting in a dosage of 1 mg/kg Cd [18]. The rats in the TQ-treated group were given TQ (50 mg/kg body weight) [13] once a day orally together with first Cd injection during the study period. At the end of the experiment, all rats were sacrificed by decapitation under ketamine-xylazine anesthesia.…”
Section: Experimental Designmentioning
confidence: 99%
“…There are several reports indicating that TQ has anti-oxidative, anti-inflammatory, anti-tumor, anti-ulcerogenic, chemopreventive, and hepatoprotective properties [10][11][12][13]. The previous studies demonstrated that TQ has a considerable protective effect against oxidative damage induced by a variety of free radical-generating agents, including nephrotoxicity produced by cisplatin [14], doxorubicin-induced nephropathy [15], carbon tetrachlorideevoked hepatotoxicity [16], and gastric mucosal injury induced by ischemia-reperfusion [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown that TQ has many pharmacological effects, including anti-oxidation and hepatoprotective effects against hepatotoxins (2,3), neuroprotective (4), anti-diabetic (5), anti-inflammatory (6), antimutagenic (7), and anti-carcinogenic (8). A recent study by Oguz et al shows that TQ inhibits common bile duct ligation (CBDL)-induced liver damage in rats including the fibrotic changes in the liver (9). So far, the hepatoprotective and antifibrotic effects of TQ is largely attributed to its anti-oxidant activity, which leads to decreased hepatocyte damage and thus decreased transactivation of hepatic stellate cells (HSCs).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of N. sativa have long been used in traditional medicine for a wide range of illnesses, including headache, dysentery, infections, obesity, back pain, bronchial asthma, hypertension and gastrointestinal problems (Al-Rowais, 2002).TQ was shown to protect against hepatic damage (Mansour et al, 2001). For instance, Ogus et al, (2012) demonstrated that oral administration of TQ relieved bile duct proliferation, periductular fibrosis and hepatic damage in bile duct-ligated rats. Lebda et al, (2011) reported that TQ prevented liver enzyme leakage and lipid peroxidation induced by D-galactosamine in rats.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ogus et al, (2012) demonstrated that oral administration of TQ relieved bile duct proliferation, periductular fibrosis and hepatic damage in bile duct-ligated rats. Lebda et al, (2011) reported that TQ prevented liver enzyme leakage and lipid peroxidation induced by D-galactosamine in rats. Nagi et al, (2010) observed that TQ protected mice against acetaminophen-induced hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%